Intelligent Robot Solution Searches The Way Out In A Maze Using Right Wall Follow Algorithm - Mochamad Ari Saptari; Sri Mutia (Faculty of Engineering, Malikussaleh University, 2018)
The following wall is one of the robotic navigation systems used in competitions, such as the Indonesian Smart Robot Contest where the wall follower type robot can follow the contours of the walls arena. This type was chosen because the race arena of the contest consisted of the walls that formed hallway and the room. Ability of a robot to complete its mission is the focus, for that reason, a reliable navigation system is necessary. Robot control cannot be separated from a control system that can process the received signal to become a command that can move the robot and perform the task as desired. By applying the Right Wall Follower algorithm, it is expected that the robot will be able to complete its mission. So it is seen as having intelligence, because it can avoid the wall in front and beside it.